Identification of RNAs bound by Hfq reveals widespread RNA partners and a sporulation regulator in the human pathogen Clostridioides difficile. Issue 11 (2nd November 2021) - Boudry, Pierre; Piattelli, Emma; Drouineau, Emilie; Peltier, Johann; Boutserin, Anaïs; Lejars, Maxence; Hajnsdorf, Eliane; Monot, Marc; Dupuy, Bruno; Martin-Verstraete, Isabelle; Gautheret, Daniel; Toffano-Nioche, Claire; et al.
ABSTRACT: Noncoding RNAs (ncRNA) have emerged as important components of regulatory networks governing bacterial physiology and virulence. Previous deep-sequencing analysis identified a large diversity of ncRNAs in the human enteropathogen Clostridioides (Clostridium) difficile . Some of them are trans -encoded RNAs that could require the RNA chaperone protein Hfq for their action. Recent analysis suggested a pleiotropic role of Hfq in C. difficile with the most pronounced effect on sporulation, a key process during the infectious cycle of this pathogen. However, a global view of RNAs interacting with C. difficile Hfq is missing. In the present study, we performed RNA immunoprecipitation high-throughput sequencing (RIP-Seq) to identify Hfq-associated RNAs in C. difficile . Our work revealed a large set of Hfq-interacting mRNAs and ncRNAs, including mRNA leaders and coding regions, known and potential new ncRNAs. In addition to trans -encoded RNAs, new categories of Hfq ligands were found including cis -antisense RNAs, riboswitches and CRISPR RNAs. ncRNA-mRNA and ncRNA-ncRNA pairings were postulated through computational predictions. Investigation of one of the Hfq-associated ncRNAs, RCd1, suggests that this RNA contributes to the control of late stages of sporulation in C. difficile . Altogether, these data provide essential molecular basis for further studies of post-transcriptional regulatory network in this enteropathogen.